2013
DOI: 10.1063/1.4789758
|View full text |Cite
|
Sign up to set email alerts
|

The effect of InGaN underlayers on the electronic and optical properties of InGaN/GaN quantum wells

Abstract: The electronic and optical properties of visible InGaN quantum-well (QW) structures grown on In0.03Ga0.97N underlayers have been investigated. A significant improvement of the QW emission is observed as a result of the insertion of the underlayers, which is associated with blueshift in the emission energy, reduced recombination lifetime, increased spatial homogeneity in the QW luminescence, and weaker internal fields inside the QWs. These are explained by partial strain relaxation evidenced by reciprocal space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…This is in line with a previous analyses of the effects of prelayers 13,14,26 where the shift in the emission energies and the changes in the radiative decay rates were attributed to a change in the in-built electric field caused by strain relaxation, but in this case our X-ray measurements eliminate this as the reason for the effects of the prelayers. To understand the observed effects, the conduction band (CB) and valence band (VB) profiles in all the samples, shown in Figure 3, were calculated using a commercially available device simulator (nextnano 3 ).…”
supporting
confidence: 93%
“…This is in line with a previous analyses of the effects of prelayers 13,14,26 where the shift in the emission energies and the changes in the radiative decay rates were attributed to a change in the in-built electric field caused by strain relaxation, but in this case our X-ray measurements eliminate this as the reason for the effects of the prelayers. To understand the observed effects, the conduction band (CB) and valence band (VB) profiles in all the samples, shown in Figure 3, were calculated using a commercially available device simulator (nextnano 3 ).…”
supporting
confidence: 93%
“…They tentatively ascribe the increased electron capture efficiency to the variation of the potential field distribution in the quantum wells. Later on, Li et al conclude that the InGaN insertion layer can reduce the internal electric field in the quantum well through observing the wavelength blueshift of the cathodoluminescence (CL) spectra and a reduced carrier lifetime derived from the time‐resolved CL spectra . More importantly, Li et al, by the electron holography, also measure and show a reduced electrostatic potential for the LED device with the InGaN insertion layer .…”
Section: Approaches For Improving the Internal Quantum Efficiencymentioning
confidence: 99%
“…Later on, Li et al conclude that the InGaN insertion layer can reduce the internal electric field in the quantum well through observing the wavelength blueshift of the cathodoluminescence (CL) spectra and a reduced carrier lifetime derived from the time‐resolved CL spectra . More importantly, Li et al, by the electron holography, also measure and show a reduced electrostatic potential for the LED device with the InGaN insertion layer . However, a most recent physical model has been developed by Ni et al , Zhang et al , Li et al , Avrutin et al , Zhang et al , and Chang et al that a reduced electron leakage is caused by the phonon‐electron scattering taking place in the InGaN insertion layer.…”
Section: Approaches For Improving the Internal Quantum Efficiencymentioning
confidence: 99%
“…Typical prelayer structures consist of 20-30 nm of intentionally Si-doped (In)GaN, which can be either a single layer or a short-period superlattice, positioned a few nanometers beneath the 1st QW. The improvements in IQE have been attributed to either increases in the radiative recombination rate 15,16,18,20,21 or decreases in the nonradiative recombination rate. 11,19 Nanhui et al 15,16 reported that the inclusion of an unintentionally doped 20 nm thick In 0.08 Ga 0.92 N layer in an InGaN/GaN multiple QW structure led to an increase in the photoluminescence (PL) intensity at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As the internal quantum efficiency (IQE) is determined by competition between radiative and non-radiative recombination processes, slower radiative recombination rates can limit the IQE. It has been reported [10][11][12][13][14][15][16][17][18][19] that the inclusion of an InGaN layer prior to the deposition of the 1st QW, a so-called "prelayer," can lead to significant improvements in the IQE of InGaN multiple QW structures and LEDs. Typical prelayer structures consist of 20-30 nm of intentionally Si-doped (In)GaN, which can be either a single layer or a short-period superlattice, positioned a few nanometers beneath the 1st QW.…”
Section: Introductionmentioning
confidence: 99%